Melatonin Supplementation Enhances Next-Day High-Intensity Exercise Performance and Recovery in Trained Males: A Placebo-Controlled Crossover Study - Nourhène Mahdi; Slaheddine Delleli; Arwa Jebabli; Khouloud Ben Maaoui; Juan Del Coso; Hamdi Chtourou; Luca Paolo Ardigò; Ibrahim Ouergui (Sports)
Background/Objectives: Sleep and recovery are critical for optimising exercise performance. However, the efficacy of melatonin supplementation in improving sleep quality and next-day physical performance remains unclear. This study examined the effects of melatonin ingestion on sleep and performance-related outcomes the following day in trained males. Methods: In a randomised, double-blind, placebo-controlled crossover study, 12 trained males (age: 21.92 ± 2.84 years) ingested 6 mg of melatonin (MEL) or a placebo (PLA) the night before performing the 5 m shuttle test (5mSRT). Before and after the 5mSRT, blood samples were collected. Peak heart rate (HRpeak) and rating of perceived exertion (RPE) were recorded throughout the test. Perceived recovery status (PRS) and delayed onset muscle soreness (DOMS) were measured before, 5 min, 24 h, 48 h, and 72 h after the test. The sleep/wake cycle was monitored during the night after ingestion. Results: Data were analysed using paired t-tests, Wilcoxon tests, and two-way ANOVAs, with significance set at p < 0.05. Compared to PLA, MEL did not modify any sleep parameters or blood markers (all p > 0.05). However, MEL improved total distance, fatigue index, the percentage decrement between sprints, and HRpeak (all p < 0.05) in the 5mSRT compared to PLA. MEL also enhanced PRS values up to 72 h post-exercise and reduced DOMS (all p < 0.05). Conclusion: In summary, 6 mg of melatonin taken at night enhanced next-day high-intensity exercise performance and improved perceived recovery up to 72 h post-exercise.